Control Mechanisms and the Relationship Life Cycle: Implications for Safeguarding Specific Investments and Developing Commitment - Jap, Sandy D.; Ganesan, Shankar (Journal of Marketing Research, 2000)
Powerful suppliers often require retailers to make significant idiosyncratic investments to improve coordination between organizations and to enhance the supplier's presence in the end market. The authors examine how a retailer might better manage the hold-up potential of these transaction-specific investments (TSIs) through the use of three control mechanisms: supplier's TSIs, the development of relational norms, and the use of explicit contracts. Moreover, the authors consider the time-dependent nature of these mechanisms by observing their effects on commitment over the course of a relationship life cycle. The results indicate that (1) a retailer's TSIs have a negative effect on its perceptions of supplier commitment; (2) a supplier's TSIs and relational norms increase the retailer's perception of supplier commitment, whereas explicit contracts are associated with perceptions of lower supplier commitment; and (3) each of the three control mechanisms moderates the negative impact of retailer investments on perceptions of supplier commitment contingent on the relationship phase. Specifically, bilateral TSIs enhance commitment in the exploration phase and a positive effect during the decline phase. The results also indicate that the retailer's perceptions of supplier commitment are positively related to its evaluation of supplier performance and satisfaction and negatively related to conflict.